Summer days and summer nights : twelve love stories - Perkins, Stephanie; Bardugo, Leigh; LaCour, Nina; Bray, Libba; Block, Francesca Lia; Perkins, Stephanie; Federle, Tim; Roth, Veronica; Skovron, Jon; Colbert, Brandy; Clare, Cassandra; Smith, Jennifer E., 1980-; et al. (St. Martin's Griffin, 2016)
Summer is the perfect time for love to bloom, and these short stories of teenagers facing the confusing maze of first love will have you dreaming of sunset strolls by the lake. The selections range from heartfelt to outlandish, as the characters find passion in some very unexpected places.